PENDAMPINGAN KEWIRAUSAHAAN MELALUI PEMBUATAN SANDAL JEPIT DI PANTI ASUHAN MUHAMMADIYAH PAMEKASAN - Siti Azizah; A. Fatikhul Amin Abdullah; Muhammad Hadiatur Rahman; Itaanis Tianah; Ahmad Imam Khairi (As-Sidanah, 2022)
Becoming an entrepreneur was not everyone's interest but the majority of people were interested in getting rich and the fastest way to get rich was becoming an entrepreneur. This was the reason for holding this mentoring program. Generally, the orphanage children had a pessimistic spirit in realizing their dreams so that sometimes it was difficult to cultivate an entrepreneurial spirit because every day their lives were supported by other parties. Therefore, in the form of entrepreneurship assistance, it seeks to foster an entrepreneurial spirit for the orphanage children through the manufacture of flip-flops as a means of triggering in starting to become entrepreneurs. .This empowerment method used Asset Based Community-driven Development (ABCD) with a target of 25 children from the Pamekasan Muhammadiyah Orphanage. From this mentoring program, a flip-flops making orphanage was formed and a production marketing community was formed to support the independence of the orphanage.